Second Tree Diameter and Tree Volume Estimation - Singh, S. P. (Indian Forester, 1981)
If precision in estimation total or partial stem volume is desired, measurement of second diameter at a certain fixed height, is necessary. Measurement of second diameter is not difficult, it can be easily done with the help of a horizontal scale mounted on a rod.